Hoover's FBI and the Fourth Estate : The Campaign to Control the Press and the Bureau's Image - Cecil, Matthew (Book collections on Project MUSE., 2014)
The complete history of the covert and sophisticated efforts of Hoover's FBI to promote a positive image and to immunize the FBI from legitimate criticisms of its abusive practices; offers a primer for our time--highlighting the dangers to civil liberties and democratic values posed by secretive and effectively unaccountable intelligence agencies.